Defibrotide improves COVID-19-related acute respiratory distress syndrome in myeloma patients after chimeric antigen receptor T-cell treatment without compromising virus-specific and anti-myeloma T-cell responses - Mehmet H. Kocoglu; Paul G. Richardson; Clifton C. Mo; Aaron P. Rapoport; Djordje Atanackovic (Haematologica, 2024)
Not available.